2012
DOI: 10.1021/ma301289v
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Confinement on Structure, Water Solubility, and Water Transport in Nafion Thin Films

Abstract: Fuel cells based on polymer electrolyte membranes (PEM) show promise as a means of energy conversion for a wide range of applications both in the transportation sector and for stationary power production due to their high charge density and low operating temperatures. While the structure and transport of bulk PEMs for fuel cell applications have been studied extensively, much less is known about these materials at interfaces and under confinement, conditions that are highly relevant in the membrane electrode a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

24
275
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(300 citation statements)
references
References 68 publications
24
275
1
Order By: Relevance
“…However, recent studies on the underlying knowledge of the structure/function relationships of ionomer thin-films in the catalyst layers are beginning to show that such an assumption is poor as discussed in more detail below. 157,[298][299][300][301][302][303][304][305] The kinetic expressions, equations 58 and 60 for the HOR and ORR, respectively, result in a transfer current between the electronicconducting (1) and ionic-conducting (2) phases (see equation 10), which is related to the current density in the two phases through equation 23 (neglecting double-layer charging)…”
Section: Catalyst-layer Modelingmentioning
confidence: 99%
“…However, recent studies on the underlying knowledge of the structure/function relationships of ionomer thin-films in the catalyst layers are beginning to show that such an assumption is poor as discussed in more detail below. 157,[298][299][300][301][302][303][304][305] The kinetic expressions, equations 58 and 60 for the HOR and ORR, respectively, result in a transfer current between the electronicconducting (1) and ionic-conducting (2) phases (see equation 10), which is related to the current density in the two phases through equation 23 (neglecting double-layer charging)…”
Section: Catalyst-layer Modelingmentioning
confidence: 99%
“…Beyond this thickness of 55 nm, free reorganization of Nafion occurs. Another study 22 also indicated the distinct characteristics of the spin coated Nafion thin films where they found that the swelling ratio, volumetric …”
mentioning
confidence: 96%
“…Recent studies have indicated that the nanostructure and morphology of thin Nafion films are different from those of thicker Nafion membrane. [14][15][16][17][18][19][20][21][22][23] One of the main reasons is the high interfacial area to volume ratio of thin films such that the substrate induced interfacial and confinement effect dominate the film morphology and properties. 24 This raises a few questions -(i) is the proton conductivity and conduction mechanism of supported thin films different than that of the freestanding membrane?…”
mentioning
confidence: 99%
“…Nafion is commonly used in power generating devices, and has excellent ionic conductivity properties. [6][7][8] Nafion is highly dependent on water, however, and performance begins to suffer in drier environments. 9 By casting the Nafion into a porous PVC material, the water-content within the PVC is hypothesized to ensure the Nafion remains hydrated to allow for adequate ionic conductivity.…”
mentioning
confidence: 99%